When you see me [large type] - Gardner, Lisa (Gardner, Lisa. Detective D.D. Warren novel, 2020)
FBI Special Agent Kimberly Quincy and Sergeant Detective D. D. Warren have built a task force to follow the digital bread crumbs left behind by deceased serial kidnapper Jacob Ness. When a disturbing piece of evidence is discovered in the hills of Georgia, they bring Flora Dane and true-crime savant Keith Edgar to a small town where something seems to be deeply wrong. What at first looks like a Gothic eeriness soon hardens into something much more sinister ... and they discover that for all the evil Jacob committed while alive, his worst secret is still to be revealed. Quincy and DD must summon their considerable skills and experience to crack the most disturbing case of their careers - and Flora must face her own past directly in the hope of saving others.